Slow-release Fertilizer Application on Silk (Falcataria moluccana Miq.) and Rice (Oryza sativa L.) Plant Growth and Yield in Agroforestry System - Madani, Hilmi Naufal; Wijayanto, Nurheni; Hartoyo, Adisti Permatasari Putri; Solikhin, Achmad (HAYATI Journal of Biosciences, 2024)
The aim of this experiment is to evaluate the impact of chitosan-NPK slow-release fertilizer (CS-NPK SRF) on the germination and growth of silk tree and rice in different planting patterns, as well as to assess the nutrient release rate of the SRF. The germination test followed a complete randomized design, incorporating a single factor (fertilizer type), namely no fertilizer (F0), SRF CS 0.5% weight 0.03 g (F1), SRF CS 0.5% 0.01 g (F2), SRF CS 0.7% 0.03 g (F3), SRF CS 0.7% 0.01 g (F4), and conventional NPK fertilizer (F5). The growth test utilized a 2-factor split-plot design, with the primary factor being the planting pattern (sengon/rice monoculture-SM/RM and sengon-rice agroforestry-AF) and the second factor being the fertilizer type. Results indicate that F2 and F4 yielded the highest germination and growth values in both plants, although not significantly different from F0. These findings suggest that CS-NPK SRF has the potential to enhance plant growth. The AF pattern exhibited lower growth compared to SM/RM, attributed to plant competition. CS-NPK SRF demonstrated a slower nutrient release (47.65% N; 85.01% P; 31.80% K) compared to conventional fertilizers. This slow release could potentially reduce nutrient loss to the environment while enhancing plant nutrient absorption.